A Systematic Literature Review on the Use of Grammarly in Improving the Writing Skills of ESL/EFL Students - Llausas, Shaina May; Ruiz, Eddielyne; Ayucan, Syndrell Mae; Evardo Jr., Orville J. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This systematic literature review examines the effectiveness of Grammarly as an Automated Writing Evaluation (AWE) tool for improving the writing skills of English as a Second Language (ESL) and English as a Foreign Language (EFL) students. Drawing on 10 studies published between 2018 and 2024, the review assesses Grammarly’s key features, benefits, and limitations. Results show that Grammarly significantly reduces grammatical errors, enhances students’ writing confidence, and fosters autonomous learning. However, challenges such as over-reliance on the tool and its limited capacity to provide comprehensive feedback on higher-order writing skills remain. The review underscores the need for further research into Grammarly’s long-term effects on writing development, particularly its efficacy across various academic disciplines and contexts.